Age, Health and Attractiveness Perception of Virtual (Rendered) Human Hair - Fink, Bernhard; Hufschmidt, Carla; Hirn, Thomas; Will, Susanne; McKelvey, Graham; Lankhof, John (Frontiers in Psychology, 2016)
The social significance of physical appearance and beauty has been documented in many studies. It is known that even subtle manipulations of facial morphology and skin condition can alter people’s perception of a person’s age, health and attractiveness. While the variation in facial morphology and skin condition cues has been studied quite extensively, comparably little is known on the effect of hair on social perception. This has been partly caused by the technical difficulty of creating appropriate stimuli for investigations of people’s response to systematic variation of certain hair characteristics, such as color and style, while keeping other features constant. Here, we present a modeling approach to the investigation of human hair perception using computer-generated, virtual (rendered) human hair. In three experiments, we manipulated hair diameter (Experiment 1), hair density (Experiment 2), and hair style (Experiment 3) of human (female) head hair and studied perceptions of age, health and attractiveness. Our results show that even subtle changes in these features have an impact on hair perception. We discuss our findings with reference to previous studies on condition-dependent quality cues in women that influence human social perception, thereby suggesting that hair is a salient feature of human physical appearance, which contributes to the perception of beauty.